Comparison of 3D reconstruction of mandible for preoperative planning using commercial and open-source software - Abdullah, Johari Yap; Omar, Marzuki; Hadi, Helmi; Husein, Adam; Rajion, Zainul Ahmad (2016)
3D printing of mandible is important for pre-operative planning, diagnostic purposes, as well as for education and training. Currently, the processing of CT data is routinely performed with commercial software which increases the cost of operation and patient management for a small clinical setting. Usage of open-source software as an alternative to commercial software for 3D reconstruction of the mandible from CT data is scarce. The aim of this study is to compare two methods of 3D reconstruction of the mandible using commercial Materialise Mimics software and open-source Medical Imaging Interaction Toolkit (MITK) software. Head CT images with a slice thickness of 1 mm and a matrix of 512x512 pixels each were retrieved from the server located at the Radiology Department of Hospital Universiti Sains Malaysia. The CT data were analysed and the 3D models of mandible were reconstructed using both commercial Materialise Mimics and open-source MITK software. Both virtual 3D models were saved in STL format and exported to 3matic and MeshLab software for morphometric and image analyses. Both models were compared using Wilcoxon Signed Rank Test and Hausdorff Distance. No significant differences were obtained between the 3D models of the mandible produced using Mimics and MITK software. The 3D model of the mandible produced using MITK open-source software is comparable to the commercial MIMICS software. Therefore, open-source software could be used in clinical setting for pre-operative planning to minimise the operational cost.